Experimental investigation on the flexural response of epoxy composites filled with environmental pollutant crump rubber. (1st March 2022) - Alblalaihid, Khalid; Shahapurkar, Kiran; Chennarayan, Venkatesh; Beyecha, Hailu; Tirth, Vineet; Algahtani, Ali; Soudagar, Manzoore Elahi M; Talugeri, Vinayak
Abstract: Flexural response of crump rubber filled epoxy composites is reported in the present work. Composites are fabricated using open mold casting technique and test specimens are evaluated at normal strain rate. Stress strain profiles of all the specimens reveal brittle mode of fracture. Modulus of crump rubber composites increase with increasing crump rubber content owing to good bonding of constituents and higher elasticity induced by crump rubber particles. Neat epoxy specimens reveal lower modulus than all the composites filled with crump rubber. Strength of all the composites are higher as compared with neat epoxy and increase as the crump rubber content is increased. Composites filled with 30 vol% of crump rubber reveals highest modulus (24%) and strength (22%) in comparison with neat epoxy and all other compositions. Scanning electron microscopy of specimens are analyzed to study the structure property correlations. Mapping of results from the current work and existing ones are compared using property chart.